Commercialisation and specialisation in artisanal fisheries: the case of Pearl Lagoon, Nicaragua (ESP) - van Anrooy, Raymon (1998)
Commercialisation and specialisation of 450 artisanal fishermen of the Pearl Lagoon, on the Atlantic Coast of Nicaragua, was measured over three consecutive years (October 1995 – September 1998). The level of commercialisation of the fishermen differed more within years than between years largely due to seasonal effects. The conventional wisdom that commercialisation leads to specialisation is not supported by the results from the present study. On the contrary, correlation analysis showed an inverse relation between commercialisation and the degree of specialisation of the fishermen, indicating that commercialisation supposedly will result in a more heterogeneous artisanal fishery production in the area.